2016
DOI: 10.1159/000442469
|View full text |Cite
|
Sign up to set email alerts
|

In Search of a Cure for Sepsis: Taming the Monster in Critical Care Medicine

Abstract: In spite of over half a century of research, sepsis still constitutes a major problem in health care delivery. Although advances in research have significantly increased our knowledge of the pathogenesis of sepsis and resulted in better prognosis and improved survival outcome, sepsis still remains a major challenge in modern medicine with an increase in occurrence predicted and a huge socioeconomic burden. It is generally accepted that sepsis is due to an initial hyperinflammatory response. However, numerous e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 161 publications
0
23
0
Order By: Relevance
“…epsis, severe sepsis, and septic shock still present unmet clinical needs with a predicted increase in occurrence and a huge socioeconomic burden as a result of population aging, increases in invasive medical procedures, the emergence of multidrug-resistant (MDR) bacteria, and the increased prevalence of chronic diseases (1). Sepsis is considered a dysregulated systemic inflammatory response syndrome caused by an infection, leading to an overwhelming and sustained proinflammatory state and, if unresolved, to multiorgan dysfunction (MOD) and death (2).…”
mentioning
confidence: 99%
“…epsis, severe sepsis, and septic shock still present unmet clinical needs with a predicted increase in occurrence and a huge socioeconomic burden as a result of population aging, increases in invasive medical procedures, the emergence of multidrug-resistant (MDR) bacteria, and the increased prevalence of chronic diseases (1). Sepsis is considered a dysregulated systemic inflammatory response syndrome caused by an infection, leading to an overwhelming and sustained proinflammatory state and, if unresolved, to multiorgan dysfunction (MOD) and death (2).…”
mentioning
confidence: 99%
“…epsis constitutes a major challenge in critical care medicine and is currently a leading cause of death in intensive care units, particularly among the elderly and immunocompromised patients (1). Studies have shown that the magnitude and quality of the immune response after an infection are better predictors of outcome than the inciting pathogen (2), yet the immune parameters that determine the outcome of sepsis in patients are not completely understood (3). The endotoxin LPS, present on the cell wall of Gram-negative bacteria, is one of the most potent activators of the immune system (4), and Gram-negative infections are the most common in the clinic (5).…”
mentioning
confidence: 99%
“…In patients with severe infectious diseases, systemic inflammatory responses, such as a cytokine storm, are part of the clinical picture [9,10]. These life-threatening conditions are often a consequence of a pathological activation of pattern recognition receptors (PRRs) by microbial pathogens [11].…”
Section: Going Fishingmentioning
confidence: 99%